Faktor Perubahan Sosial Terhadap Eksistensi Konsep Perseroan Perorangan di Indonesia - Nirwana Theresya Siboro (International Forum of Researchers and Lecturers, 2026)
Social change in Indonesia has had a significant impact on various aspects of life, one of which is reflected in the emergence of the Sole Proprietorship Company concept under Law No. 6 of 2023 on Job Creation. This framework allows individuals to establish a Limited Liability Company, particularly to support micro and small enterprises (MSEs). The innovation is not merely an adaptation of global practices but also a response to the need to strengthen economic independence. This study applies an interdisciplinary method with normative and socio-legal approaches to examine the provisions of the Sole Proprietorship Company by integrating social change factors underlying its necessity, despite substantive differences from conventional Limited Liability Companies. The analysis explores legal legitimacy and social readiness, concluding that social transformation drives the demand for this concept. Thus, regulations should be refined to remain simple and effective while encouraging MSEs to use it as a legal safeguard.